2021
DOI: 10.1001/jamapediatrics.2020.6130
|View full text |Cite
|
Sign up to set email alerts
|

Acute Knee Injuries in Children and Adolescents

Abstract: ne-third of all musculoskeletal complaints in primary care officesareduetokneepain. 1 Upwardof60millionchildrenaged 6 to 18 years participate in organized sports each year in the US. 2 Parallelingthislevelofparticipationisasignificantnumberofsportsrelated injuries, with the knee being one of the most commonly injured joints: up to 54% of young athletes have knee pain annually. 3 There are anestimated2.5millionsports-relatedkneeinjuriesinadolescentseach year,and60%ofsports-relatedsurgeriesinhighschoolathletesin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…However, our data did demonstrate that the knee joint is by far the most operated on, with 98.2% of respondents qualifying as a knee specialist and reporting that the knee constituted a mean of 52.1% of an individual’s practice. This was consistent with the expectations, as 54% of young athletes have knee pain annually9 and knee injuries account for 60% of high school sport–related surgeries performed 10. Of these injuries, the anterior cruciate ligame is the most injured ligament in the knee, and procedures to reconstruct this ligament have increased significantly 11…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, our data did demonstrate that the knee joint is by far the most operated on, with 98.2% of respondents qualifying as a knee specialist and reporting that the knee constituted a mean of 52.1% of an individual’s practice. This was consistent with the expectations, as 54% of young athletes have knee pain annually9 and knee injuries account for 60% of high school sport–related surgeries performed 10. Of these injuries, the anterior cruciate ligame is the most injured ligament in the knee, and procedures to reconstruct this ligament have increased significantly 11…”
Section: Discussionsupporting
confidence: 88%
“…This was consistent with the expectations, as 54% of young athletes have knee pain annually 9 and knee injuries account for 60% of high school sport-related surgeries performed. 10 Of these injuries, the anterior cruciate ligame is the most injured ligament in the knee, and procedures to reconstruct this ligament have increased significantly. 11 One of the more surprising findings in this survey was that the hip surgery constituted a similar percentage of an individual's practice as shoulder surgery (13.9% vs. 15.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Some injuries occur more often than others. As in adults, the knee and ankle joints are damaged more often than other regions [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Knee injury is a common disease affecting people's health and quality of life in the 21st century, and researchers have found that FMN also plays a beneficial role in improving healing after knee injury. Under normal circumstances, knee joint injury mainly includes joint destruction, dislocation and fracture caused by traumatic violence, or it can occur as a result of degenerative disease caused by long‐term overuse of the joint in older patients (Brittberg et al, 2016; MacDonald et al, 2021). Currently, we typically treat acute knee injury caused by violent trauma with surgical treatment, so drug treatment of chronic or secondary knee injury caused by nonviolent factors such as aging‐related knee strain and posttraumatic OA was the focus of our study (Arden et al, 2021; Takeda et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With more extensive investigation, the advantages of these medicines have been gradually discovered by researchers (Li et al, 2021;Lyu et al, 2021;Tang et al, 2021). In recent years, FMN, an isofla- (Brittberg et al, 2016;MacDonald et al, 2021).…”
Section: Discussionmentioning
confidence: 99%